Textbook of medical physiology - Guyton, Arthur C. (Philadelphia : Saunders, 1991)
This textbook offers current authoritative coverage that is easy to read and understand. It provides coverage of molecular and cellular physiology, long-term arterial pressure regulation and hypertension, the neurophysiology of vision, the body's resistance to infection, and physiology from a quantitative perspective. The new edition integrates the latest information throughout the text, and helps students relate physiology to other aspects of medicine and analyze problems.
Unit I. Introduction to Physiology: The Cell and General Physiology -- Ch. 1. Functional Organization of the Human Body and Control of the "Internal Environment" -- Ch. 2. The Cell and Its Function -- Ch. 3. Genetic Control of Protein Synthesis, Cell Function, and Cell Reproduction -- Unit II. Membrane Physiology, Nerve, and Muscle -- Ch. 4. Transport of Substances Through the Cell Membrane -- Ch. 5. Membrane Potentials and Action Potentials -- Ch. 6. Contraction of Skeletal Muscle -- Ch. 7. Excitation of Skeletal Muscle: A. Neuromuscular Transmission and B. Excitation-Contraction Coupling -- Ch. 8. Contraction and Excitation of Smooth Muscle -- Unit III. The Heart -- Ch. 9. Heart Muscle; The Heart as a Pump -- Ch. 10. Rhythmical Excitation of the Heart -- Ch. 11. The Normal Electrocardiogram -- Ch. 12. Electrocardiographic Interpretation of Cardiac Muscle and Coronary Blood Flow Abnormalities: Vectorial Analysis -- Ch. 13. Cardiac Arrhythmias and Their Electrocardiographic Interpretation -- Unit IV. The Circulation -- Ch. 14. Overview of the Circulation; Medical Physics of Pressure, Flow, and Resistance -- Ch. 15. Vascular Distensibility, and Functions of the Arterial and Venous Systems -- Ch. 16. The Microcirculation and the Lymphatic System: Capillary Fluid Exchange, Interstitial Fluid, and Lymph Flow -- Ch. 17. Local Control of Blood Flow by the Tissues; and Humoral Regulation -- Ch. 18. Nervous Regulation of the Circulation, and Rapid Control of Arterial Pressure -- Ch. 19. Dominant Role of the Kidney in Long-Term Regulation of Arterial Pressure and in Hypertension: The Integrated System for Pressure Control -- Ch. 20. Cardiac Output, Venous Return, and Their Regulation -- Ch. 21. Muscle Blood Flow and Cardiac Output During Exercise; the Coronary Circulation and Ischemic Heart Disease -- Ch. 22. Cardiac Failure -- Ch. 23. Heart Valves and Heart Sounds; Dynamics of Valvular and Congenital Heart Defects -- Ch. 24. Circulatory Shock and Physiology of Its Treatment -- Unit V. The Kidneys and Body Fluids -- Ch. 25. The Body Fluid Compartments: Extracellular and Intracellular Fluids; Interstitial Fluid and Edema -- Ch. 26. Urine Formation by the Kidneys: I. Glomerular Filtration, Renal Blood Flow, and Their Control -- Ch. 27. Urine Formation by the Kidneys: II. Tubular Processing of the Glomerular Filtrate -- Ch. 28. Regulation of Extracellular Fluid Osmolarity and Sodium Concentration -- Ch. 29. Integration of Renal Mechanisms for Control of Blood Volume and Extracellular Fluid Volume; and Renal Regulation of Potassium, Calcium, Phosphate, and Magnesium -- Ch. 30. Regulation of Acid-Base Balance -- Ch. 31. Micturition, Diuretics, and Kidney Diseases -- Unit VI. Blood Cells, Immunity, and Blood Clotting -- Ch. 32. Red Blood Cells, Anemia, and Polycythemia -- Ch. 33. Resistance of the Body to Infection: I. Leukocytes, Granulocytes, the Monocyte-Macrophage System, and Inflammation -- Ch. 34. Resistance of the Body to Infection: II. Immunity and Allergy -- Ch. 35. Blood Groups; Transfusion; Tissue and Organ Transplantation -- Ch. 36. Hemostasis and Blood Coagulation -- Unit VII. Respiration -- Ch. 37. Pulmonary Ventilation -- Ch. 38. Pulmonary Circulation; Pulmonary Edema; Pleural Fluid -- Ch. 39. Physical Principles of Gas Exchange; Diffusion of Oxygen and Carbon Dioxide Through the Respiratory Membrane -- Ch. 40. Transport of Oxygen and Carbon Dioxide in the Blood and Body Fluids -- Ch. 41. Regulation of Respiration -- Ch. 42. Respiratory Insufficiency -- Pathophysiology, Diagnosis, Oxygen Therapy -- Unit VIII. Aviation, Space, and Deep-Sea Diving Physiology -- Ch. 43. Aviation, High-Altitude, and Space Physiology -- Ch. 44. Physiology of Deep-Sea Diving and Other Hyperbaric Conditions -- Unit IX. The Nervous System: A. General Principles and Sensory Physiology -- Ch. 45. Organization of the Nervous System; Basic Functions of Synapses and Transmitter Substances -- Ch. 46. Sensory Receptors; Neuronal Circuits for Processing Information -- Ch. 47. Somatic Sensations: I. General Organization; the Tactile and Position Senses -- Ch. 48. Somatic Sensations: II. Pain, Headache, and Thermal Sensations -- Unit X. The Nervous System: B. The Special Senses -- Ch. 49. The Eye: I. Optics of Vision -- Ch. 50. The Eye: II. Receptor and Neural Function of the Retina -- Ch. 51. The Eye: III. Central Neurophysiology of Vision -- Ch. 52. The Sense of Hearing -- Ch. 53. The Chemical Senses -- Taste and Smell -- Unit XI. The Nervous System: C. Motor and Integrative Neurophysiology -- Ch. 54. Motor Functions of the Spinal Cord; The Cord Reflexes -- Ch. 55. Cortical and Brain Stem Control of Motor Function -- Ch. 56. The Cerebellum, the Basal Ganglia, and Overall Motor Control -- Ch. 57. The Cerebral Cortex; Intellectual Functions of the Brain; and Learning and Memory -- Ch. 58. Behavioral and Motivational Mechanisms of the Brain -- The Limbic System and the Hypothalamus -- Ch. 59. States of Brain Activity -- Sleep; Brain Waves; Epilepsy; Psychoses -- Ch. 60. The Autonomic Nervous System; and the Adrenal Medulla -- Ch. 61. Cerebral Blood Flow; the Cerebrospinal Fluid; and Brain Metabolism -- Unit XII. Gastrointestinal Physiology -- Ch. 62. General Principles of Gastrointestinal Function -- Motility, Nervous Control, and Blood Circulation -- Ch. 63. Propulsion and Mixing of Food in the Alimentary Tract -- Ch. 64. Secretory Functions of the Alimentary Tract -- Ch. 65. Digestion and Absorption in the Gastrointestinal Tract -- Ch. 66. Physiology of Gastrointestinal Disorders -- Unit XIII. Metabolism and Temperature Regulation -- Ch. 67. Metabolism of Carbohydrates, and Formation of Adenosine Triphosphate -- Ch. 68. Lipid Metabolism -- Ch. 69. Protein Metabolism -- Ch. 70. The Liver as an Organ -- Ch. 71. Dietary Balances; Regulation of Feeding; Obesity and Starvation; Vitamins and Minerals -- Ch. 72. Energetics and Metabolic Rate -- Ch. 73. Body Temperature, Temperature Regulation, and Fever -- Unit XIV. Endocrinology and Reproduction -- Ch. 74. Introduction to Endocrinology -- Ch. 75. The Pituitary Hormones and Their Control by the Hypothalamus -- Ch. 76. The Thyroid Metabolic Hormones -- Ch. 77. The Adrenocortical Hormones -- Ch. 78. Insulin, Glucagon, and Diabetes Mellitus -- Ch. 79. Parathyroid Hormone, Calcitonin, Calcium and Phosphate Metabolism, Vitamin D, Bone, and Teeth -- Ch. 80. Reproductive and Hormonal Functions of the Male (and Function of the Pineal Gland) -- Ch. 81. Female Physiology Before Pregnancy; and the Female Hormones -- Ch. 82. Pregnancy and Lactation -- Ch. 83. Fetal and Neonatal Physiology -- Unit XV. Sports Physiology -- Ch. 84. Sports Physiology -- Index.
Includes bibliographical references and index.
Keywords: Human physiology; Physiology, Pathological; Physiology; Physiologie humaine; Physiopathologie; Physiologie; Human physiology; Physiology, Pathological; Fysiologie; Menselijk lichaam; Humans -- Physiology